Aplicación móvil multiplataforma para el control de inventario en la Boutique Nicoleth, utilizando la plataforma Xamarin - Chacon Robalino, Carlos David (2023)
This current research project has as the main objective to develop a mobile multiplatform app at the Nicoleth Boutique in Riobamba, to do the stocktaking control, which is very important and fundamental in a commercial organization since it allows to carry out a control of its incomes and expenses of the supplies and products setting a detailed order because of its value and importance. For the mobile multiplatform app, it was used Xamarin, due to, it permits to share codes and share the user interface between platforms besides that, to obtain a modern application and with a high performance for the mobile operating system Android and iOS. Additionally, it was used the SCRUM methodology which consists of five stages, maintaining an agile and collaborative work for the application production. On the other hand, through the rule ISO/IEC 25010 an evaluation of the mobile app performance was carried out, using the efficient characteristic which consist on certain sub characteristics like: temporal behavior and utilization resources. For the performance test the mobile app it was used the Apache JMeter software in which some simulations with repetitions were done in real time, it was developed for Android and iOS devices. With the obtained results, through the rule app we could make evident that the app performance is excellent, obtaining grades like 8,43 for Android and 8,48 with iOS, for that we could verify that results effective the use of the application at the moment to realize the control process of the stocktaking, achieving also the compatibility for Android y iOS.